Microarchitectural Abnormalities Are More Severe in Postmenopausal Women with Vertebral Compared to Nonvertebral Fractures - Stein, Emily M. (Endocrine Society, 2012)
BACKGROUND: Abnormal bone microarchitecture predisposes postmenopausal women to fragility fractures. Whether women with vertebral fractures have worse microarchitecture than those with nonvertebral fractures is unknown. METHODS: Postmenopausal women with a history of low trauma vertebral fracture (n = 30) and nonvertebral fracture (n = 73) and controls (n = 120) had areal bone mineral density of lumbar spine, total hip, femoral neck, 1/3 radius, and ultradistal radius measured by dual-energy x-ray absorptiometry. Trabecular and cortical volumetric bone mineral density and microarchitecture were measured by high-resolution peripheral quantitative computed tomography of the distal radius and tibia. Finite element analysis estimated whole bone stiffness. RESULTS: Mean age of subjects was 68 ± 7 yr. Groups were similar with respect to age, race, and body mass index. Mean T-scores did not differ from controls at any site except the ultradistal radius (vertebral fracture, 0.6 sd lower; nonvertebral fracture, 0.4 sd lower). Compared to controls, women with vertebral fractures had lower total, cortical, and trabecular volumetric density, lower cortical thickness, trabecular number and thickness, greater trabecular separation and network heterogeneity, and lower stiffness at both radius and tibia. Differences between women with nonvertebral fractures and controls were similar but less pronounced. Compared to women with nonvertebral fractures, women with vertebral fractures had lower total and trabecular density, lower cortical thickness and trabecular number, and greater trabecular separation and heterogeneity at the tibia. Whole bone stiffness tended to be lower (P = 0.06). Differences between fracture groups at the radius were not statistically significant. CONCLUSION: Women with vertebral fractures have more severe trabecular and cortical microarchitectural deterioration than those with nonvertebral fractures, particularly at the tibia.